Neutrophil Cytosolic Factor 1 in Dendritic Cells Promotes Autoreactive CD8+ T Cell Activation via Cross-Presentation in Type 1 Diabetes - Liu, Chao; Whitener, Robert L.; Lin, Andrea; Xu, Yuan; Chen, Jing; Savinov, Alexei; Leiding, Jennifer W.; Wallet, Mark A.; Mathews, Clayton E. (Frontiers in Immunology, 2019)
Aims: Reactive oxygen species (ROS) are critical in driving the onset of type 1 diabetes (T1D). Ablation of ROS derived from phagocytic NADPH oxidase 2 is protective against autoimmune diabetes in non-obese diabetic (NOD) mice. However, the mechanisms of NADPH oxidase 2-derived ROS in T1D pathogenesis need to be elucidated. Here, we have examined the role of Ncf1 (the regulatory subunit of NADPH oxidase 2) in dendritic cells (DC). Results:Ncf1-mutant DCs exhibit reduced ability to activate autoreactive CD8+ T cells despite no difference in co-stimulatory molecule expression or pro-inflammatory cytokine production. When provided with exogenous whole-protein antigen, Ncf1-mutant NOD DCs showed strong phagosome acidification and rapid antigen degradation, which lead to an absence of protein translocation into the cytoplasm and deficient antigenic peptide loading on MHC Class I molecules. Innovation: This study demonstrates that Ncf1 (p47phox) is required for activation and effector function of CD8+ T cells by acting both intrinsically within the T cell as well as within professional antigen presenting cells. Conclusion: ROS promote CD8+ T cell activation by facilitating autoantigen cross-presentation by DCs. ROS scavengers could potentially represent an important component of therapies aiming to disrupt autoantigen presentation and activation of CD8+ T cells in individuals at-risk for developing T1D.